Newborn screening and presymptomatic treatment of metachromatic leukodystrophy - Laugwitz, Lucia; Mechtler, Thomas P.; Janzen, Nils; Oliva, Petra; Kasper, Andrea-Romana; Teunissen, Charlotte E.; Bürger, Friederike; Janda, Joachim; Döring, Michaela; Weitz, Marcus; Lang, Peter; Martin, Pascal; et al. (The New England journal of medicine, 2024)
In a pilot program in which 109,259 newborns were screened for metachromatic leukodystrophy, blood-spot samples were obtained for analysis and three newborns with MLD were identified, which made presymptomatic treatment possible.
Gesehen am 05.03.2025